Pullulan-Stabilized Silver Nanoparticles -Their Synthesis, Characterization and Application as Bactericidal Agents - V. S. Rama Krishna Ganduri & , Ushakiranmayi Mangamuri, Vijayalakshmi Muvva, Sudhakar Poda (Journal of Applied Pharmaceutical Science, 2016)
A rapid method for Pullulan-stabilized silver nanoparticles (PuAgNPs) synthesis has been developed. Different concentrations of Pullulan and Silver nitrate and effects of reaction time, pH was used to investigate the synthesis of silver nanoparticles. The synthesized Pu-AgNPs were first screened and identified using surface plasmon peaks of UV–VIS spectroscopy. The research results indicated that the surface plasmon resonance peaks were observed between 410–460 nm wavelengths in UV-VIS spectroscopy studies. The morphology of the synthesized AgNPs proved a variation in spherical shape and polydispersed with an average size of 10-55 nm, using TEM. Further, five characteristic peaks confirmed the presence of elemental silver and the crystalline structure of silver nanoparticles from XRD analysis. From FTIR spectra, stretching vibrations of hydroxyl (O-H), carbonyl (C=O) and C=C stretches exhibits the reduction and stabilization of AgNPs. Further, clear zones of inhibition (about 10-25 mm) against four bacterial pathogens obtained in the antibacterial studies for the synthesized PuAgNPs. The experimental results demonstrated that pullulan could be used as reducing and stabilizing agent for formation of AgNPs and can be used as redoubtable bactericidal agents.
Keywords: Pu-AgNPs, TEM, XRD, FTIR, Bactericidal agents.